(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to identify the determinants of leadership in improve sound governance in education sector institutions of the South Nation Nationalities People Region (SNNPR). The study was used a quantitative method (QUAN). It used inferential approach for their appropriateness for defining the research problem. The survey questionnaire collected from 660 participants purposefully and randomly selected from the nine zones, nine Woredas, and nine town administrations sampled education institutions of the SNNPR. Multistage sampling techniques (purposive, random sampling techniques) were instrumental. The logit model and multicollinearity effect were employed were instrumental. It has been found that sampled education sector institutions were experiencing various leadership determinants that hindered the promotion of sound governance, on the logit model. It can be concluded that, despite some policy initiatives and directives introduced by the regional government, the study identifies various determinants of leadership that effecting the promotion of sound governance. The researcher, thus, specified some significant policy implications to promote sound governance in SNNPR education sector institutions: establish strong accountability mechanism, granting autonomy, strengthening anti-corruption agencies and law, promoting management development program, promoting equity and fairness institutionalizing transparency system, trans, revisit policy directives and initiatives, promoting integrity, the merit-based nomination of education officials and adopt empowerment and management programs are some of the policy implications